Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species - Wu, Xuwen; Xu, Kuidong (Zootaxa, 2017)
Sternaspidae is one of the most common groups of polychaetes in the South China Sea, where however, the knowledge of its diversity and distribution is insufficiently understood and reports of the European species Sternaspis scutata are misidentifications. Based on the examination of material deposited in the Marine Biological Museum of the Chinese Academy of Sciences, we made a comprehensive investigation on the sternaspid polychaetes in the northern South China Sea. Five species belonging to two genera are described: Petersenaspis salazari sp. nov., Sternaspis radiata sp. nov., S. spinosa Sluiter, 1882, S. sunae sp. nov. and S. wui sp. nov. A taxonomic key to ten species of Sternaspidae found in the South China Sea is provided.